Experimental and numerical research on a new semi-rigid joint for single-layer reticulated structures. (1st November 2016) - Ma, Huihuan; Ren, Shan; Fan, Feng
Highlights: A new joint, named the bolt-column (BC) joint, is developed. A series of test was conducted with different parameters. The whole moment-rotation curves were obtained. 3D FE model of the joint was established and verified by the test results. The influence rules of the parameters on the performance of the joint are obtained. Abstract: Recent challenge for large-span single-layer reticulated structures is the development of a new joint that can provide these structures with adequate stiffness while satisfying various important requirements, such as easy assembly on a construction site. In this paper, a new semi-rigid joint system, which is referred to as the bolt-column (BC) joint, is developed. A series of tests was performed considering different thicknesses of the side plates, pretension forces and diameters of the bolts. A three-dimensional finite element (FE) model of the joint was developed to evaluate the bending stiffness, moment resistance, rotational capacity and failure mode of the joint. A comparison between the computations and experiments highlights the degree of accuracy of the proposed FE models. The moment-rotation curves, which can be introduced in the analysis of the structure, were obtained. The stiffnesses, strengths, rotation behaviours, and failure modes of the joints are carefully compared and discussed. Based on the results, the influence rules of the parameters on the mechanical behaviour of the new joint are obtained, which are helpful for engineers and designers. The results indicate that the application of this type of joint in construction practice is promising. The experimental results are employed to calibrate the finite element models, which are used to conduct a parametric study.